71.4k views
2 votes
Solve for h(x)=x(x+3)(x-2)

User Penfold
by
4.3k points

1 Answer

3 votes

Answer:

Your answer is:

If you are solving to find x then your answer would have been: x = 0 , -3 , 2

If you are solving to find the x and y intercepts your answer is: ↓

x-intercept(s): (0,0) (-3,0) (2,0)

y-intercept(s): (0,0)

If you are solving to find roots your answer is: x = 0 , -3 , 2

If you want the graph look below ↓

Explanation:

Hope this helped : )

Solve for h(x)=x(x+3)(x-2)-example-1
User Tegan
by
4.8k points